2009
DOI: 10.1111/j.1601-183x.2009.00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Species differences in cannabinoid receptor 2 (CNR2 gene): identification of novel human and rodent CB2 isoforms, differential tissue expression and regulation by cannabinoid receptor ligands

Abstract: Cannabinoids, endocannabinoids and marijuana activate two well-characterized cannabinoid receptors (CB-Rs), CB1-Rs and CB2-Rs. The expression of CB1-Rs in the brain and periphery has been well studied, but neuronal CB2-Rs have received much less attention than CB1-Rs. Many studies have now identified and characterized functional glial and neuronal CB2-Rs in the central nervous system. However, many features of CB2-R gene structure, regulation and variation remain poorly characterized in comparison with the CB1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
157
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(160 citation statements)
references
References 43 publications
2
157
0
1
Order By: Relevance
“…The data also showed that the mRNA levels of CB2R-B in the hippocampus were almost undetectable (Fig. 1A), in accord with the results from other brain areas such as the prefrontal cortex, striatum and brain stem (Liu et al, 2009). …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The data also showed that the mRNA levels of CB2R-B in the hippocampus were almost undetectable (Fig. 1A), in accord with the results from other brain areas such as the prefrontal cortex, striatum and brain stem (Liu et al, 2009). …”
Section: Resultssupporting
confidence: 86%
“…Two pairs of primers were designed to detect two splicing variants, which have been named CB2R-A (NM_009924.3) and CB2R-B (XM_006538515.1) (Liu et al, 2009) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…However, recent findings also suggest alternative receptor coupling of the CB 2 receptor or unidentified cannabinoid receptors and splice variants. (77) The difficulty of determining that effects are in fact specifically cannabinoid receptor–mediated is complicated by the constitutive activity of both cannabinoid receptors that may sustain biological processes, and a lack of neutral antagonists for both receptors. Future studies are likely to determine the molecular pathway in which CB 2 agonists successfully inhibit breast cancer proliferation and cytokine-chemokine secretion.…”
Section: Discussionmentioning
confidence: 99%
“…The CB 2 variants are generated through the use of alternate promoters located upstream of the major coding exon 3 53 . The gene CB 2A is initiated from the more distal promoter and includes exons 1a and 1b spliced to exon 3, while CB 2B is initiated from the more proximal promoter and includes exon 2 spliced to exon 3.…”
Section: Functional Gpcr Alternative Splice Variantsmentioning
confidence: 99%